(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Newly graduated students experience challenges in searching for a job, and it is a challenge that should not be taken lightly. These challenges are often felt through rejection letters or emails sent by companies to applicants, even during uncomfortable interviews. Finding a job can be stressful, to say the least. It can be overwhelming to the point that newly graduated people feel hopeless in seeking a job that suits their character, skills, and qualifications. The results showed that the highest age range is 19–22 years old, with 60%, and the lowest is 27 and above, with 7.3%. In terms of course, BTVTED has 23%, and the lowest are BSCPE and BPED, which both have 3.6%. According to the results, problems encountered in terms of lack of experience have a weighted average of 2.36; lack of communication skills have a weighted average of 2.32; and lack of seminars and training have a weighted average of 2.29. The results for possible behavioral preparedness of graduating students to cope with job seeking in terms of practicing interviews have a weighted average of 3.36, preparing a curriculum vitae or resume is 3.39, and seeking professional consultation has a weighted average of 2.25. The implication of this study is to propose a career guidance program to help graduate students succeed in their job-seeking process. The study shows that the problems encountered by graduating students are mostly a lack of communication, which requires proper training for formal communication. The study shows that the possible behavioral preparedness of graduating students is most likely practicing interviews and preparing a curriculum vitae or resume. With that, the researchers will utilize a carefully crafted career guidance program for graduating students.